Synthesis of 5-Benzylidine-3-a-carboxy Ethyl Rhodanines and Study of their Anticancer Activity Against HeLa Cell Lines and Antibacterial Activity Against MRSA - Sundaram, Kaveri; Ravi*, Subban (Asian Journal of Chemistry, 2013)
Seven novel 5-benzylidine-3-a-carboxy ethyl rhodanines were synthesized and evaluated for their in vitro anticancer activity against HeLa cell line by MTT assay method and antibacterial activity against Escherichia coli and Bacillus cereus by MIC method. The antibacterial activity was also evaluated against multidrug-resistant Staphylococcus aureus (MRSA). The synthesized compounds were characterized by IR, UV, 1H, 13C and MS spectral data. Among the synthesized compounds, 3b was found to be more potent with HeLa cancer line with an IC50 value of 22.96 μM and 3f against all the bacteria in the antibacterial activity with an MIC value of 80 μg/mL.